Smooth Endoplasmic Reticulum Clusters in Oocytes From Patients Who Received Intracytoplasmic Sperm Injections Negatively Affect Blastocyst Quality and Speed of Blastocyst Development - Wang, Xue; Xiao, YaLing; Sun, ZhengYi; Zhen, JingRan; Yu, Qi (Frontiers in Physiology, 2021)
Findings regarding the relationship between smooth endoplasmic reticulum clusters (SERCs) in oocytes and blastocyst development have been conflicting. In this study, the effects of SERCs on blastocyst quality and the speed of blastocyst development were evaluated. Patients who received intracytoplasmic sperm injections at our reproductive centre from 2016 to 2020 were retrospectively analysed. SERC (+) oocytes (n = 217) and SERC (–) oocytes (n =822), as well as SERC (+) cycles (n = 146) and SERC (–) cycles (n = 1951) were compared. There was no significant difference in embryological, clinical, and neonatal outcomes between the SERC (+) and SERC (-) cycles. The fertilisation rate (73.9%) and the speed of blastocyst development (44.4%) were significantly lower (P < 0.05) in SERC (+) oocytes than in unaffected counterparts (86.2% and 63.4%, respectively). Furthermore, the proportion of blastocysts with trophectoderm grade C was significantly higher in the SERC (+) oocyte group than in the SERC (–) oocyte group (73.3% vs 55.9%, P < 0.05). After adjusting for age, years of infertility, endometriosis, stimulation protocols (GnRHa), and male infertility, multiple logistic regression analysis revealed that the presence of SERCs in the oocytes significantly affected the speed of blastocyst development (odds ratio, 2.812; 95% CI, 1.257–6.292; P = 0.012). These findings suggest that the presence of SERCs in oocytes may negatively affect blastocyst quality and the speed of blastocyst development.